United Nations development cooperation: Challenges and reforms at the end of the 1990s - Stephan Klingebiel (Deutsches Institut für Entwicklungspolitik (DIE), 1998)
The development cooperation (DC) of the United Nations (UN) at the end of the 1990s can be described and assessed as follows: The UN is an important pillar of multilateral DC. The organization is endowed with some fundamental presuppositions (universality, a high level of legitimation, good presence at country level) needed to deal with important development- cooperation tasks. This is above all true for politically sensitive areas and global challenges. Still, UN development cooperation is often perceived as weak and lacking in effectiveness. This is due on the one hand to shortcomings such as institutional fragmentation, inadequate financial mechanisms, and deficient quality standards, which constitute a tangible obstacle to effectiveness and efficiency. On the other hand, another factor responsible for this state of affairs is an often poor UN image that is largely based on exaggerated criticism. Following several decades in which reform debates at times proved intransigent and relatively unproductive, Secretary- General Kofi Annan in particular is now providing important new impulses aimed at reshaping the whole of UN development cooperation. Moreover, individual UN agencies like the United Nations Development Programme (UNDP) have, in the 1990s, embarked on an ambitious course of reform. Though the efforts undertaken by the Secretary- General toward improving the coordination of UN activities, enhancing quality, mobilizing financial resources, etc. are on the whole reasonable, they are nevertheless by no means sufficient in that certain important structural problems can be solved only by the member states themselves. To what extent the reform process already initiated will in the coming years be characterized by stagnation or by dynamism will largely depend on the policies of the UN member states. The central obstacles to reforms consist here in disinterest and anti-UN invectives on the part of many governments. What is instead called for is a tangible member- state commitment to reforms. There is often a lack of reform concepts, of the will to set aside national interests (for instance in personnel policy), and of a sufficient level of willingness to put the Secretary-General's overall reform program into practice. Germany can play a more active role in the reform debate as a means of strengthening UN development cooperation. Not least on account of the level of German contributions, a greater German commitment - including an indirect commitment via the European Union (EU) - could provide some important impulses toward reform.
Keywords: 330